Future Directions of Percutaneous Biliary Interventions - Riaz, Ahsun; Salem, Riad (Seminars in Interventional Radiology, 2021)
We are at an exciting cross-road in biliary interventions. While other services such as surgery and gastroenterology have learned to use imaging guidance to improve the safety and efficacy of their procedures, it is time for interventional radiologist to learn endoscopic interventions to achieve the same. The future of interventional radiologists in managing patients with biliary disease depends on (1) increasing comfort of our procedures, (2) publishing our data on biliary interventions, and (3) increasing collaboration with other services to manage biliary disease. We need to appropriately understand the limitations of interventional radiology to help guide the future directions of our specialty in this very interesting space.
Keywords: biliary interventions; future directions; endoscopy